Shared network‐level functional alterations across substance use disorders: A multi‐level kernel density meta‐analysis of resting‐state functional connectivity studies. (21st June 2022) - Taebi, Arezoo; Becker, Benjamin; Klugah‐Brown, Benjamin; Roecher, Erik; Biswal, Bharat; Zweerings, Jana; Mathiak, Klaus
Abstract: An increasing number of neuroimaging studies indicate functional alterations in cortico‐striatal loops in individuals with substance use disorders (SUD). Dysregulations in these circuits may contribute to drug‐seeking and drug‐consuming behaviour by impeding inhibitory control, habit formation, and reward processing. Despite evidence of network‐level changes in SUD, a shared pattern of functional alterations within and between spatially distributed brain networks has not been systematically investigated. The present meta‐analytic investigation aims at identifying common alterations in resting‐state functional connectivity patterns across different SUD, including stimulant, heroin, alcohol, cannabis, and nicotine use. To this aim, seed‐based whole‐brain connectivity maps for different functional networks were extracted and subjected to multi‐level kernel density analysis to identify dysfunctional networks in individuals with SUD compared with healthy controls. In addition, an exploratory analysis examined substance‐specific effects as well as the influence of drug use status on the main findings. Our findings indicate a hypoconnectivity pattern for the limbic, salience, and frontoparietal networks in individuals with SUD as compared with healthy controls. The default mode network additionally exhibited a complex pattern of hypo‐ and hyperconnectivity across the studies. The observed disrupted connectivity between networks in SUD may associate with deficient inhibitory control mechanisms that are thought to contribute to excessive craving and automatic drug‐related behaviour as well as failure in substance use cessation. The identified network‐based alterations in SUD represent potential treatment targets for neuromodulation, for example, network‐based real‐time functional magnetic resonance imaging (fMRI) neurofeedback. Such interventions can evaluate the behavioural relevance of the identified neural circuits. Abstract : Our study provides meta‐analytical evidence on network‐level alterations in substance use disorder (SUD). Our findings show altered connectivity within and between distributed brain networks including the salience, limbic, frontoparietal, and default‐mode network in SUD compared with healthy controls.